Household enterprises in Vietnam : survival, growth, and living standards - Vijverberg, Wim P. M., 1955- 1955- (Policy research working paper, 2002)
Two-fifths of the household enterprises that operated in Vietnam in 1993 were still in business in 1998, after five years of rapid economic growth. Constrained by lack of education, credit, and effective demand in poor areas, and squeezed by the lure of wage labor in rich areas, household enterprises are most prominent when agriculture is declining in importance but before the formal sector becomes established